Design and development of a programmable painting robot for houses and buildings - Aris, A. K. M.; Iqbal, Parvez; Ramli, A. R.; Shamsuddin, S (Universiti Teknologi Malaysia, 2005)

(untitled)
Nowadays robots are widely used in many applications such as military, medical application, factories, entertainment, automobile industries etc. However, the application of robot is still not widely implemented in construction industry. In construction industry, robots are designed to increase speed and improve the accuracy of construction field operations. It can also be used to do hazardous and dangerous jobs in construction. For example, currently house painting is done manually. This process can be simplified using a special dedicated robot. It is very difficult and troublesome for human being to work in an upright position, especially for painting, cleaning and screwing in the ceiling for a long time. Painting in an upright position is also very dangerous for the eyes. To overcome this difficulty, a programmable painter robotic system is proposed, designed and developed. This paper describes all the processes that are involved in designing and constructing the proposed painter robot. The system is divided into two main parts namely hardware and software. In hardware part, mechanical design, fabrication, electrical and electronics system are described and in software part, control algorithm is explained. The testing results indicate that the performance of the painter robot is better compared with that of using manual painting technique.